2013
DOI: 10.1136/oemed-2012-101060
|View full text |Cite
|
Sign up to set email alerts
|

Obliterative bronchiolitis in fibreglass workers: a new occupational disease?: Table 1

Abstract: A rare, potentially fatal disease occurring in six workers laying up fibreglass with styrene resins from five different worksites suggests that work exposures were the cause of their OB. The precise agent responsible awaits identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
1
26
0
5
Order By: Relevance
“…There were no strong associations between cumulative potential styrene exposure and a priori or elevated causes of death and none of the excess mortality was for causes of death considered likely a priori. The COPD excess points to a need for an in-depth investigation of respiratory disease and occupational styrene exposure, particularly in light of recent reports associating styrene reinforced plastic manufacturing with the lung disease bronchiolitis obliterans 36 37. Our study of cancer incidence in this cohort may clarify some of the cancer mortality results.…”
Section: Discussionmentioning
confidence: 76%
“…There were no strong associations between cumulative potential styrene exposure and a priori or elevated causes of death and none of the excess mortality was for causes of death considered likely a priori. The COPD excess points to a need for an in-depth investigation of respiratory disease and occupational styrene exposure, particularly in light of recent reports associating styrene reinforced plastic manufacturing with the lung disease bronchiolitis obliterans 36 37. Our study of cancer incidence in this cohort may clarify some of the cancer mortality results.…”
Section: Discussionmentioning
confidence: 76%
“…Cullinan et al 1 reported six obliterative bronchiolitis (OB) cases with plausible correlation with fiberglass-reinforced plastics (FRP) fabrication. Five of them were boat builders and one worked for a cooling-tower manufacturer.…”
mentioning
confidence: 99%
“…Biomarkers for transplant-related obliterative bronchiolitis are being evaluated in occupational cohorts at risk for occupational lung disease. Within the occupational lung disease community, the occurrence of obliterative bronchiolitis without recognized accidental over-exposure is a paradigm that contributed to recognition of deployment hazards for U.S. soldiers (King et al, 2011) and reporting of obliterative bronchiolitis cases in boat builders and others using plastic-reinforced fiberglass (Cullinan et al, 2013; Chen et al, 2013; Kreiss, 2013). The need to improve the quality of commercial spirometry for medical surveillance of excessive decline in lung function led to development of longitudinal decline freeware, retraining requirements for technicians performing occupational spirometric surveillance, and improved NIOSH-certified training courses.…”
Section: Toxicologic and Public Health Outcomesmentioning
confidence: 99%